Multistage antiplasmodial activity of hydroxyethylamine compounds, in vitro and in vivo evaluations. Issue 58 (25th September 2020) - Sharma, Neha; Gupta, Yash; Bansal, Meenakshi; Singh, Snigdha; Pathak, Prateek; Shahbaaz, Mohd; Mathur, Raman; Singh, Jyoti; Kashif, Mohammad; Grishina, Maria; Potemkin, Vladimir; Rajendran, Vinoth; et al.
Abstract : Malaria, a global threat to the human population, remains a challenge partly due to the fast-growing drug-resistant strains of Plasmodium species. Abstract : Malaria, a global threat to the human population, remains a challenge partly due to the fast-growing drug-resistant strains of Plasmodium species. New therapeutics acting against the pathogenic asexual and sexual stages, including liver-stage malarial infection, have now attained more attention in achieving malaria eradication efforts. In this paper, two previously identified potent antiplasmodial hydroxyethylamine (HEA) compounds were investigated for their activity against the malaria parasite's multiple life stages. The compounds exhibited notable activity against the artemisinin-resistant strain of P. falciparum blood-stage culture with 50% inhibitory concentrations (IC50 ) in the low micromolar range. The compounds' cytotoxicity on HEK293, HepG2 and Huh-7 cells exhibited selective killing activity with IC50 values > 170 μM. The in vivo efficacy was studied in mice infected with P. berghei NK65, which showed a significant reduction in the blood parasite load. Notably, the compounds were active against liver-stage infection, mainly compound 1 with an IC50 value of 1.89 μM. Mice infected with P. berghei sporozoites treated with compound 1 at 50 mg kg −1 dose had markedly reduced liver stage infection. Moreover, both compounds prevented ookinete maturation and affected the developmental progression of gametocytes. Further, systematic in silico studies suggested both the compounds have a high affinity towards plasmepsin II with favorable pharmacological properties. Overall, the findings demonstrated that HEA and piperidine possessing compounds have immense potential in treating malarial infection by acting as multistage inhibitors.